Perlindungan Hukum terhadap Pengguna Jasa Pinjaman Online dalam Analisis Hukum Pidana - Putri, Refa Alya (UM Purwokerto Press, 2024)
Legal protection can be interpreted as the government's effort to protect those who do not feel a sense of justice in the life of the nation or state, on the other hand, consumer protection can be interpreted as the government's efforts to protect consumer rights, as an institution that manages the supervisory and regulatory system for the financial services industry, the Financial Services Agency must make greater efforts to protect consumers from legal action. Consumer protection is not the same as legal protection, as a research method, the author uses a normative legal approach in discussing this article ,the research specification for this legal article is descriptive analysis using data types in the form of primary and secondary data.